Environmental policy and firm behaviour: Abatement investment and location decisions under uncertainty and irreversibility - Anastasios Xepapadeas (Fondazione Eni Enrico Mattei (FEEM), 1999)
The paper explores abatement investment and location responses to environmental policy, which takes the form of emission taxes or tradable emission permits and subsidies against the costs of abatement investment, under uncertainty and irreversibility. Uncertainty is associated with output price, environmental policy parameters, or technological parameters. Irreversibility is related to abatement expenses, and movements to a new location. Uncertainty is modelled by Itô stochastic differential equations, and the problem is analysed by using optimal stopping methodologies. Continuation intervals during which firms do not engage in abatement investment or relocate and intervals during which firms take the irreversible decision of undertaking abatement expenses or relocating are defined. Free boundaries are characterised for a variety of cases that include output price uncertainty, policy uncertainty expressed both in terms of continuous fluctuations of permit prices and unpredictable policy changes, and combined policy and technological uncertainty. An optimal environmental policy is defined as the combination of policy parameters that makes the free boundary corresponding to the profit maximisation problem coincide with the free boundary corresponding to a social optimisation problem.
Keywords: L12; Q25; Q28; 330; Umweltpolitik; Umweltmanagement; Umweltschutzinvestition; Betriebliche Standortwahl; Theorie; Entscheidung bei Unsicherheit